Association between louse abundance and MHC II supertypes in Galápagos mockingbirds - Vlček, Jakub (Jihočeská univerzita, 2023)
In this thesis I describe association between abundance of ectoparasitic lice and supertypes of major histocompatibility complex in mockingbirds of Galápagos islands. I report a significant association between several supertypes and the lice abundance. Lice abundance was correlated also with heterocyte to lymphocyte ratio, an immunogenetic index reflecting rate of immune stress. This scientific contribution is valuable, because ectoparasite abundance in birds was rarely contrasted to MHC and other immune indices.
Association between louse abundance and MHC II supertypes in Galápagos mockingbirds
Keywords: ectoparasite; immunity; genes; major histocompatibility complex; ectoparasite; immunity; genes; major histocompatibility complex